Age-related changes in the central auditory system - Ouda, Ladislav; Profant, Oliver; Syka, Josef (Cell and tissue research, 2015)
Aging is accompanied by the deterioration of hearing that complicates our understanding of speech, especially in noisy environments. This deficit is partially caused by the loss of hair cells as well as by the dysfunction of the stria vascularis. However, the central part of the auditory system is also affected by processes accompanying aging that may run independently of those affecting peripheral receptors. Here, we review major changes occurring in the central part of the auditory system during aging. Most of the information that is focused on age-related changes in the central auditory system of experimental animals arises from experiments using immunocytochemical targeting on changes in the glutamic-acid-decarboxylase, parvalbumin, calbindin and calretinin. These data are accompanied by information about age-related changes in the number of neurons as well as about changes in the behavior of experimental animals. Aging is in principle accompanied by atrophy of the gray as well as white matter, resulting in the enlargement of the cerebrospinal fluid space. The human auditory cortex suffers not only from atrophy but also from changes in the content of some metabolites in the aged brain, as shown by magnetic resonance spectroscopy. In addition to this, functional magnetic resonance imaging reveals differences between activation of the central auditory system in the young and old brain. Altogether, the information reviewed in this article speaks in favor of specific age-related changes in the central auditory system that occur mostly independently of the changes in the inner ear and that form the basis of the central presbycusis.
Keywords: magnetická rezonanční tomografie; Immunohistochemistry; stárnutí; Magnetic Resonance Imaging; Aging; sluchová dráha; Hearing Loss; nedoslýchavost; Auditory Pathways; imunohistochemie